The polymorphism rs4705342 in the promoter of miR-143/145 is related to the risk of epithelial ovarian cancer and patient prognosis - Zhao, Jian; Zuo, Weiwei; Zhang, Yue; He, Caiyun; Zhao, Wei; Meng, Tongyu (Frontiers in Oncology, 2023)
Abstract Objective: To evaluate the effects of two genetic variants in the promoter of the miR-143/145 cluster on the risk of epithelial ovarian cancer (EOC) and the prognosis of EOC patients. Study design: Genotypes were determined by the polymerase chain reaction and ligase detection reaction method in 563 EOC patients and 576 healthy women. The expression of miR-143 and miR-145 were detected by quantitative real-time polymerase chain reaction (qRT–PCR) in fifty-two EOC tissues. Results: The rs4705342 CC genotype frequencies in EOC patients were higher than those in the controls (P = 0.014). Furthermore, the CC genotype of rs4705342 was associated with an advanced FIGO stage of EOC patients (P = 0.046). Patients with the rs4705342 CC genotype had shorter progression-free survival (PFS) and overall survival (OS) times than those carrying the TT genotype in multivariable analysis adjusting for clinical variables (HR = 1.30, 95% CI = 1.04-1.62, P = 0.020; HR = 1.33, 95% CI = 1.05-1.70, P = 0.020). In addition, the miR-145 levels were lower in EOC tissues with the rs4705342 CC genotype than in those with the TT genotype (P = 0.005). Conclusion: The CC genotype of rs4705342 was related to an increased risk of EOC and poor prognosis of EOC patients, and rs4705342 may serve as a molecular marker for predicting the development of EOC and the clinical outcome of EOC patients.